IMPROVEMENT OF METHODS OF ENSURING ENERGY EFFICIENCY OF ENERGY-INTENSIVE EQUIPMENT IN THE MINING AND METALLURGICAL INDUSTRY - Mavlonov Jonibek Ashurovich (American Journals Publishing, 2025)
In the current stage of socioeconomic development and amidst significantly rising energy prices, the task of efficient energy use in various sectors of the country's economy is particularly important. The development of the mining and processing industry—increasing processing volumes, deeper deposits, declining ore quality and quantity, steadily rising energy prices, and reducing energy cost is one of the most pressing challenges of world. Therefore, improving methods for ensuring the energy efficiency of energy-intensive equipment in the mining and metallurgical industry is a pressing issue.
Keywords: Control system, ball mill, thyristor, electric drive.